Low‐Threshold Whispering Gallery Mode Lasing from Self‐Assembled Microspheres of Single‐Sort Conjugated Polymers. Issue 10 (16th May 2017) - Kushida, Soh; Okada, Daichi; Sasaki, Fumio; Lin, Zhan‐Hong; Huang, Jer‐Shing; Yamamoto, Yohei
Abstract : Low‐threshold organic microlasers are demanded for advanced optical applications such as nano/micrometer scale memory, sensing, and communication tools, and further valuable for future electrically driven laser applications. In this paper, it is demonstrated that various highly fluorescent conjugated polymers self‐assemble to form single‐component microspheres that exhibit, upon femtosecond pumping to a single microsphere, whispering gallery mode (WGM) lasing with blue, green, and red emission colors. In particular, the microsphere consisting of polyfluorene shows the lowest threshold fluence as low as 1.5 µJ cm −2 and high photostability against successive pumping of >10 5 pulse. The threshold fluence is further reduced by one fourth (0.37 µJ cm −2 ) by mounting the microspheres on an Ag‐coated substrate, where a mirror effect of the Ag layer enhances efficiency of the photoluminescence confinement with a minor effect of plasmonic near‐field. Considering the intrinsic charge injection and transport properties, π‐conjugated polymer microsphere resonators will be possible materials for electrically pumped WGM luminescence. Abstract : Self‐assembled, single‐component conjugated polymer microspheres exhibit whispering gallery mode lasing upon femtosecond laser pumping with the lasing threshold as low as one micro Joule per square centimeter. The threshold fluence is further reduced by one fourth by mounting the microspheres on an Ag‐coated substrate, which is among the lowest for that ever reported with dye‐doped polymer lasers.